Electron Donor-Acceptor Spirobi[cyclopenta[2,1-b:3,4-b’] dithiophene Derivatives as Precursors of Electrodeposited Regioregular Thiophene-based Polymers - Minudri, Daniela (2021)
A series of conjugation extended push-pull derivatives of 4,4′-spirobi[cyclopenta[2,1-b : 3,4-b′]dithiophene] were synthesized and fully characterized, in which each perpendicularly aligned cyclopenta[2,1-b : 3,4-b′]dithiophene features a pendant dicyanovinylene as an electron acceptor and a thiophene as an electron donor. The electrochemical and photophysical properties of the new molecules, which differ from each other for the presence and/or location of an additional n-hexyl chain on the pendant thiophene unit, were investigated, as well as their susceptibility to electrochemical polymerization. The substitution arrangement of the monomers was found to exert significant influence on the outcome of the electropolymerization process and on the optoelectronic properties and morphological film characteristics of the new regioregular materials obtained.